Analisis Pengaruh Tarif Bongkar Muat, Unit Shipscall serta Inflasi terhadap Bongkar General Cargo Kapal Pelayaran Rakyat - Santoso, Herman Budi (Akutansi Bisnis & Manajemen ( ABM ), 2007)
: Dock of Kalimas Surabaya have operated as dock clinch ships him Sea transport of People and also as ship loading and unloading since 19th century, that far before the building of Tanjung Perak Port in 1910 by Indies Dutch Government ans till now although Tanjung Perak Port have moderned, with operated Terminal Petikemas Surabaya (TPS) since 1992 to make balance the growth of International sea transport systems change over from conventional sea transport become container sea transport, but role of Dock Kalimas with its sailing boat still significant as interregional sea transport. That proved by data of Unit Ship’s Call (is Unit), ships od Pelra 2006 since January – December is 66; 55; 78; 76; 90; 103; 81; 78; 99; 79; 64; 50. In Dock of Kalimas that destined for Pelra’s ship clinch and loading – unloading various commodity and also specially General Cargo, so the unload volume of General Cargo influenced by various internal factor and external factor that is Loading-Unloading Tariff variable (X1) with regression coefficient 0.275, variable of Unit Ship’s Call (X2) with regression coefficient 98.307, and Inflation variable (X3) with regression coefficient 255.379.